DPA Printing (printing and design services) / Mohd Wishal Nasrullah Azahar … [et al.] - Nasrullah Azahar, Mohd Wishal Nasrullah; Beti, Christyn Belaja; Zamri, Mohd Firdaus; Mohd Mervyn Dublin, Ahmad Alim; Dio, Douglas (2019)
Our company's name is The DPA Printing Enterprise. We use that name because it was inspired by our course when we're studying in the same university at University Technology Mara and to show our cooperation as partnership of this company we agree set The DPA Printing as our company's name. Our main activity is about designing and printing. Therefore, we are not only do printing service such as t-shirt printing, banner and so on. But our company also provide designing service such as designing t-shirt for student activity according to our customer tastes and desire. Our main objective is providing printing and design service to our customer. We are not only provide those services that have been state but we also provide trophies, medals, mug designing, sling bag and souvenir. Our company also use an app for ease our customer to set an order and so on. The business was founded by our general manager that is Mr Mohd Wishal Nasrullah Azahar and cooperate with another four partner. They are Mr Christyn Belaja Anak Beti as the financial manager, Mr Mohd Firdaus Bin Zamri as the marketing manager, Mr Ahmad Alim Bin Mohd Mervyn Dublin as the administration manager and Mr Douglas Anak Dio as the operational manager. The premise is located at Lot 36, Lorong Desa Ilmu 22H2, Fasa 25, 94300 Kota Samarahan, Sarawak. The location is strategic and near to our target customer that is students, civil servants and teachers. Our location is near to the educational institute such as UITM, UNIMAS, ILPKS and so on. We have registered our company on 23 November 2018 and we start our business on 1 January 2019 the same date as our company date of business commencement.